Anti-neutrophil cytoplasmic autoantibodies associated vasculitis – Clinical profile and outcomes - Kavya Devi Nunna; Phani Kumar Devarasetti; Rajendra Vara Prasad Irlapati; Liza Rajasekhar (Indian Journal of Rheumatology, 2018)
Background: Studies on antineutrophil cytoplasmic autoantibodies-associated vasculitis (AAV) from India are scarce. The aim of the present study was to characterize the profile of AAV and experience with rituximab in ocular granulomatous with polyangiitis (GPA) in our cohort. Methods: Clinical, laboratory, and treatment details of AAV from January 2010 to May 2017 were noted. Continuous variables were reported as mean and standard deviation (SD). In GPA, clinical variables between survivors and nonsurvivors were compared using independent sample t-test and Fisher's exact test. Cox regression analysis was done to estimate the hazard ratios. Our cohort of GPA was compared with other large single-center cohorts from India, USA, Germany, and France. Results: Thirty-one patients were diagnosed to have AAV. Seventeen were females. GPA was most common phenotype (23/31). Mean (SD) age at onset was 39.8 (15.7) years. Median (IQ) time to diagnosis was 6 (22) months. The most common manifestations in GPA were ocular (n = 20) and lower respiratory tract (n = 13). Mean (SD) Birmingham Vasculitis Activity Score (BVAS) at disease onset was 9.4 (6.9). Pulse methylprednisolone with cyclophosphamide was used as induction regime followed by maintenance with azathioprine. Rituximab was given to four patients with refractory GPA. Six patients succumbed to illness. Remission was achieved in 19/25 survivors. Mean (SD) BVAS at disease onset was significantly higher in nonsurvivors (17.6 ± 10.2) compared to survivors (9.4 ± 4.9) (P = 0.018). Higher proportion of renal involvement was seen in nonsurvivors (P = 0.03). There was three-fold increased mortality with renal and lung involvement. In addition, the risk of death increases by 1.13 fold with each point increase in BVAS score. Conclusion: Ocular involvement was higher in our GPA cohort. Baseline BVAS, renal, and lung involvement predicts poor prognosis in GPA. Sustained remission with rituximab was seen in all patients with refractory ocular disease.